Love and Truth in Social Involvement of the Church - Henryk Szmulewicz (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
This study begins with a brief outline of the essence of the whole encyclical Caritas in veritate . Benedict XVI expresses the desire for „the dialogue with the world”. He understands this dialogue as a special kind of the service of the Church towards eternal love and truth, fully revealed in Christ. The dialogue of the Church with the world, in the spirit of love and truth, is accomplished every day at the level of so-called official relations. There are numerous opinions that in the past the Church repeatedly neglected the dialogue with the world. Indeed, the Church historians point out the existence of examples of the fall of the authority of the Holy See in particular countries and circumstances. Similarly, the Church is the sign of objection in the contemporary world. Instructed by past experiences the Church is aware that what is necessary for the renewal of culture and society, is evangelical love and truth.